Key challenges for rural destinations to meet the expectations of Generation Z travellers - Mondok, Anita; Zámbó, Zsófia (Acta Carolus Robertus, 2022)
Generation Z travellers, who typically do not yet have their own income, constitute the youngest group of tourism demand, who are often ignored by destination management organizations or tourism service providers. However, they play a key role in shaping consumer demand and act as drivers of developments in destinations. Generation Z is almost redefining what it means to travel - their unique needs and specific destination preferences can set the future direction of tourism development.All of these findings provide a basis for conducting primary data collection by involving the members of the generation in a questionnaire survey in order to learn about the relationship of the Hungarian respondents (N=212 people) with IT, their travel habits, the method of financing their trips, and their communication preferences. Based on the results obtained, the characteristics of the future demand for rural destinations, expectations and preferences for the range of expected services and experiences emerge. All of this helps in shaping the future direction of tourism development in rural destinations.